2020
DOI: 10.3389/fimmu.2019.03130
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Models and Tools for the in vivo Study of Neutrophils

Abstract: Neutrophils are the most abundant leukocytes in human blood and critical actors of the immune system. Many neutrophil functions and facets of their activity in vivo were revealed by studying genetically modified mice or by tracking fluorescent neutrophils in animals using imaging approaches. Assessing the roles of neutrophils can be challenging, especially when exact molecular pathways are questioned or disease states are interrogated that alter normal neutrophil homeostasis. This review discusses the main in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 221 publications
(294 reference statements)
0
62
0
1
Order By: Relevance
“…To further determine whether neutrophils contribute to circulating miR-223, we performed neutrophil depletion experiments. Injection of anti-Ly6G or anti-Gr-1 antibodies have been widely used to deplete neutrophils; however, these approaches suffer from limitations of low efficiency or specificity, especially during chronic depletion (28). Indeed, we found that treatment of HFD-fed mice with anti-Gr-1 for two weeks only slightly reduced circulating neutrophils (data not shown).…”
Section: Evidence That Hepatocyte Uptake Of Mir-223-enriched Evs Is Pmentioning
confidence: 77%
“…To further determine whether neutrophils contribute to circulating miR-223, we performed neutrophil depletion experiments. Injection of anti-Ly6G or anti-Gr-1 antibodies have been widely used to deplete neutrophils; however, these approaches suffer from limitations of low efficiency or specificity, especially during chronic depletion (28). Indeed, we found that treatment of HFD-fed mice with anti-Gr-1 for two weeks only slightly reduced circulating neutrophils (data not shown).…”
Section: Evidence That Hepatocyte Uptake Of Mir-223-enriched Evs Is Pmentioning
confidence: 77%
“…Studies suggesting a beneficial role for neutrophils in influenza virus infection typically rely on mouse models to monitor the impact of neutrophil depletion before or after infection with influenza viruses. For many years, the monoclonal antibody (mAb) RB6-8C5 was the standard for neutrophil depletion [100]. However, RB6-8C5 binds both Ly6G expressed on neutrophils, and Ly6C present on neutrophils, dendritic cells, and other populations of lymphocytes and monocytes [100].…”
Section: The Beneficial Roles Of Neutrophils During Influenza Virus Infectionmentioning
confidence: 99%
“…The not selectivity of specific leukocyte subsets and the high excitation required to detect fluorescent signal caused photodamage and altered leukocyte adhesion and microvascular fluidity (Saetzler et al, 1997). Later studies used genetically modified mice that were generated as tools for in vivo imaging of neutrophil behavior (Stackowicz et al, 2019). In the Lys-EGFP + mice, both neutrophils and monocyte are fluorescently labeled, neutrophils exhibiting high fluorescence, while monocytes are only dim green (Faust et al, 2000).…”
Section: Introductionmentioning
confidence: 99%